BİR HATİP VE EĞİTİMCİ OLARAK VANÎ MEHMED EFENDİ, HAYATI, EDEBÎ KİŞİLİĞİ, ESERLERİ. - KILIÇ, Yasin (Electronic Turkish Studies)
The 17th century scientist and statesman Mehmed Efendi who is known as Vanî in the history, (Katip Çelebi, 1943:1131) lived during the reign of Sultan İbrahim and Sultan Mehmed the fourth (Hammer, 1986:111). The date of his birth is not exactly known. (Bursalı, 1915:462). He has been named as Vanî since his father was from Van. (Pazarbaşı, 1988:IX). In this study, in addition to Vanî Mehmed Efendi's life, It has been determined that sufficient research has been done about his opinions on Sufism; but on the other hand, his feature about being a preacher and educationist has not been investigated in an adequate level. Vanî Mehmed Efendi's feature about preaching and educationist has been researched. Method Our study consists of three sections. In the first section, Vanî Mehmed Efendi's biography has been handled. In the second section, Vanî Mehmed Efendi's preaching, educationist features, literal personality, principles and ideas have been analyzed under the headlines of his literal personality, his ability of persuasion, nationalism, his opinion about Sufism and Sufists, his struggle against the bad, his students, his language and style. Examples especially about his preaching and education have been presented from his products and the events he experienced. In the third section, the writer's products have been introduced and the research has been ended. In the research, descriptive method and document analysis models have been used. Vanî Mehmed Efendi started his education in Van and continued in Tebriz. He completed his education in Karabağ. (Pazarbaşı, 1988:4). He worked as a preacher and hodja in Erzurum (Parmaksızoğlu, 1976:407). He was appreciated by Köprülüzade Fazıl Ahmed Pasha who was appointed as a governor in September 1659. When Pasha became a Grand vizier, he invited him to Istanbul and he introduced him with Sultan Murad the fourth (Pazarbaşı, 2003:458). Vanî Efendi gained Sultan Mehmed's the fourth confidence in a very short time. (Hammer, 1986:112-166-180). Vanî Mehmed Efendi was appointed as a preacher and hâce-i sultan to Yeni Cami in 1665. (Beliğ, 1287:209). Born in İzmir a rabbi- Jewish reverend named Sabatay Seviappeared claiming that he was Messiah and since he was blamed for challenging the Emperor, he was judged by a committee in which Vanî Mehmed Efendi took part on 24th September 1666. Sevi who claimed that he was Messiah was asked to show a miracle but as he was not able to show any sign of miracle he accepted to become a Muslim (Hammer, 1986:159-160; Ahmed Badi Efendi, 2014:464). Vanî Efendi had a mosque built in Bursa Kestel and it carried his name- Vanî Mehmed Efendi. (Ötüken, vd, 1986: 28-30). As the army preacher, Vanî Mehmed Efendi attended Vienna siege the second leaded by Merzifonlu Kara Mustafa Pasha. When the Ottoman Empire lost the war, he was seen responsible for the defeat and relegated to Kestel and finally died there in 1685. He was buried in the garden of the mosque he had built. (Pazarbaşı, 1988: 45). Not only did Vanî Mehmed Efendi improve himself in religious but also in literal, mysticism and political subjects. Furthermore, he gained a great reputation in the public and became one of the scholars who was mostly respected in the society. Uşşakî zâde, saw an ability equal to prodigy with Vanî Efendi and expressed that he was gifted in born by God. (Uşşâkî-zâde, no. 949:269) One of his students İshâk b. Hasan Tokâdî states that Vanî Efendi completed 22 disciplines in his book called "Nazmu'l-Ulum. Tokadi resembles his teacher to a sea of advice. (Pazarbaşı, 2003:458; Pazarbaşı, 1988: 44). Hammer exemplifies Vanî Efendi's ability to preach as follows: An epidemic of plague appeared in cities like Damascus, İstanbul, Aleppo, Edirne. At the same time, earthquakes happened in most of the Turkish cities as a result many people lost their lives in those disastrous events. After these events, he made people and Sultan Mehmed the fourth cry. (Hammer, 1989:165). The events mentioned above can be regarded as the examples of his ability in education and addressing of Vanî Efendi. In his product called Münşeat, Vanî, used a quite kind tone in his letters he wrote to the statesmen. He addressed the statesmen with the expressions like respect, encouragement, and appreciation which can be classified as motivation in education (Konuk, 2001: 27). Vanî Efendi joined the second Vienna siege as the preacher of the army and he had an impressive effect on the soldiers (Öztuna, 1983:XI, 292). Vanî Efendi thought that Turkish people deserved Allah's and prophet's compliments. By reminding the saying in the verse; "another nation may be sent instead of you'' Vanî, pointed at the replacement of some Muslims who behaved unwillingly to join Tebuk military expedition, by the Turkish. (Tevbe:38-39) (Pazarbaşı, 1990:361-370; Vanî, Süleymaniye Ktp: Arisü'l Kur'an, vr 543). During the period when Vanî Efendi was appointed in the place, some of his applications like banning tobacco and alcohol, closing some cafes and pubs caused disapproval among Christians. Hammer (1986: 92), Vanî Efendi, mentioned that he was closely interested in sufism and he tried to worship after analyzing the books of the sufists and understanding the doctrines (Beliğ 1287:209) but when he was at his forty by reading fiqh boks he realized that he was misled by the previous sufists as a result he gave up dealing with Sufism (Pazarbaşı, 1994:466). The feeling of responsibility is the key element to the order and unity of a society (Güven, 2014:513). It may be claimed that Vanî Efendi, who had responsibility feeling, had a educational side by raising awareness against tobacco and alcohol and encouraging governments to close down the cafes that damaged the order of the state. In his Turkish written products, Vanî Mehmed Efendi used Arabic and Persian words very intensively. Moreover, ıt could be said that he used a complicated language and descriptive narration in his products. Finally, he preferred a punned, selective and an artistic utterance in his writings. Conclusion We have reached the conclusions below: 1. Two master thesis have been prepared about Vanî Mehmed Efendi's products (Pazarbaşı, 1988; Konuk, 2001), and at the same time, an encyclopedic matter has been prepared (Pazarbaşı, 2003) . 2. Because of the different views about Sufism 3 articles have been brought into light which narrate the arguments between Vanî and Niyazi-i Mısri. (Bilkan, 2005; Pazarbaşı, 1994; Kavruk, 2009) In these articles, the views of both scientists have been employed. 3. Vane created products in the fields of interpretation, fıqh, history and literature. Especially due to his product called Arâisü'l- Kur'an, Quran has been interpreted from a different point of view. 4. With his preaches in different parts of Ottoman Empire, Vanî raised awareness and he impressed the statesmen deeply. Münşeat may be regarded as one of the most distinguished products of Vanî for his efficiency in addressing. 5. In his product called "Arâisü'l Kur'an" he made some deductions about Turkish people from Quran that's why he was accepted as the first Turkish nationalist by some scholars. In this study, the focus has been on the writer's educationalist and preaching ability and ıt has been concluded that Vanî is an outstanding scholar for the Turkish nation. Within this study, ıt is thought that this study will give way to further investigations about Vanî and his precious products.